External root resorption: Arrested or progressing? - Vatanpour, Mehdi; Javidi, Maryam; Zarei, Mina; Shirazian, Shiva (Iranian Endodontic Journal, 2009)
External root resorption may be an uncontrolled phenomenon, and the most known interventions have no effect. Even progressive external root resorption may not be controlled by long term Ca(OH)2 therapy. Currently, there are no treatment options for vital tooth that suffer from root resorption. This invasive resorption can lead to extraction of the tooth. The use of new technologies such as low power laser may control this type of resorption.